Effectiveness of Pursed Lip Breathing To Changes Respiratory Rate In The Patients With COPD In Lung Room RSUD Dr R. Sosodoro Djatikoesomo Bojonegoro 2017 - Mulyani, SRI; Muslima, Evita; yohastuti, Feris (AKADEMI KESEHATAN RAJEKWESI BOJONEGORO, 2018)
Shortness of breath in COPD occurs due to dynamic hyperinflation that increases weight with increased respiratory rate. Efforts that can be done on COPD that occur respiratory pattern disorders is pursed lip breathing exercises. The number of COPD patient was second rank after tuberculosis in 2016 in the lung room RSUD Dr R Sosodoro Djatikoesomo Bojonegoro total 160 patient. The study aims to determine Effectiveness of Pursed Lip Breathing To Changes Respiratory Rate In The Patients With COPD In Lung Room RSUD Dr R. Sosodoro Djatikoesomo Bojonegoro 2017. Research method using pra experimental one group pre post test design. The population is all COPD patients in the lung room of the month of may-july total 30 patients. While the sample of 20 patients taken using purposive sampling technique. Take data using observation, then done editing, coding, scoring and tabulation of data analyzed by using crosstab.The result of cross tabulation was obtained after pursed lip breathing majority decreased respiratory rate that is 20 respondents (100%). So it can be conclude that pursed lip breathing is effective to changes respiratory rate in the patients with COPD In Lung Room RSUD Dr R. Sosodoro Djatikoesomo Bojonegoro. Recommended for respondents should do pursed lip breathing exercise at least 2 twice a day every morning and afternoon with a durations of 10 minutes.